Learning in the 21st Century Education Era: Problems of Mathematics Teachers in the Use of Information and Communication Technology-Based Media - Niswatun Hasanah; Siti Inganah; Bhaskoro Prasetyo Adi Maryanto (Universitas PGRI Madiun, 2023)
This study uses a descriptive qualitative approach. The type of research used in this research is a case study. This research was conducted in the 2022/2023 academic year. This research was conducted at MAN 2 Malang. 7 research subjects were math teachers at schools who taught grades X to XII. Collecting data in this study using observation and interview techniques. The data analysis technique used in this study is the data analysis technique proposed by Miles & Hubberman (Reduction, Presentation, Conclusion). The results of the problems found: 1) some students do not yet have a mature understanding of mathematical concepts and do not have the knowledge to learn mathematics from previous classes, and 2) lack of motivation to learn, 3) the use of instructional media is less effective in stimulating student learning motivation, and 4) the use of learning methods is not adapted to the characteristics of students. 5) Teachers with 2 to 5 years of teaching experience at the beginning tend to use learning media actively, while teachers who have been teaching for a long time with more than 10 years of teaching experience tend to use traditional learning methods. 6) Teachers' capacity to use ICT is still lacking, and teachers' capacity to integrate technology into teaching practice is lacking. In other words, teachers are not proficient with computers and lack ICT equipment and infrastructure. 7) schools with existing facilities such as LCDs, computers, and the internet are rarely used in the learning process